Effect of Dietary Zinc Supplementation on Some Seminal Plasma Characteristics of Broiler Breeders’ Males - Amen, Mahmood H.M.; Al-Daraji , Hazim J. (International Journal of Poultry Science, 2011)
The aim of the present study was to evaluate the effect of zinc (Zn) as feed additive on certain seminal plasma traits of broiler breeders’ males. A total of 36 Cobb 500 broiler breeders males, 45 weeks old were used in this study. These birds were randomly distributed equally into four dietary treatments with three replicates each. Each treatment group constituted 9 males. Treatment groups were as following: T1: Birds fed the basal diet without any addition of zinc (0 Zn) (control), T2: Birds fed diet supplemented with 50 mg Zn (pure zinc)/kg of diet, T3: Birds fed diet supplemented with 75 mg Zn (pure zinc)/kg of diet and T4: Birds fed diet supplemented with 100 mg Zn (pure zinc)/kg of diet. Results revealed that adding zinc to the diet of roosters (T2, T3 and T4) resulted in significant (p<0.05) decrease in seminal plasma glucose at 54, 58, 62 and 66 weeks of age and protein during 54, 58 and 66 weeks of age and concerning the total means of these two traits in comparison with T1 group. However, feeding diets containing zinc (T2, T3 and T4) resulted in significant (p<0.05) increase in seminal plasma Alkaline Phosphatase (ALP) activity and significant (p<0.05) decrease in seminal plasma Aspartate Aminotransferase (AST) and Alanine Aminotransferasr (ALT) activity and cholesterol concentration during 58 and 66 weeks of roosters age and with relation to the total means of these traits as compared to T1 group. In conclusion, supplementation of the broiler breeder males with zinc caused significant improvement in seminal plasma traits included in this study. Therefore, dietary zinc supplementation can be used as active tool for enhance reproductive performance of roosters.